Pathophysiological mechanisms of integrated regulation of water-sodium homeostasis: from cellular dysfunction of Na-K-ATPase to dysregulation of systemic volume control: a systematic review - Gozhenko, Anatoliy; Zukow, Walery; Gozhenko, Olena; Saensus, Mykhailo; Vitiukov, Oleksandr (Journal of Education, Health and Sport, 2025)
Background: Water-sodium homeostasis regulation is a fundamental physiological process that ensures cellular function maintenance, extracellular fluid volume, and arterial pressure. Despite decades of research, the integrated understanding of the dual sodium regulatory system remains incomplete, limiting the development of effective therapeutic approaches for cardiovascular and renal diseases. Objective: To conduct a systematic review and meta-analysis of evidence regarding integrated dual regulation of water-sodium homeostasis, including cellular mechanisms (digitalis-like compounds and Na-K-ATPase) and systemic mechanisms (natriuretic peptides and neurohormonal volume regulation), with assessment of their pathophysiological interactions and clinical implications. Methods: A systematic search was conducted in PubMed/MEDLINE, Embase, Cochrane Library, Web of Science, and Scopus databases (1957-2025) according to PRISMA 2020 guidelines. Experimental studies, clinical trials, and observational studies investigating sodium regulation mechanisms at cellular and systemic levels were included. Study quality was assessed using RoB 2.0, ROBINS-I, and Newcastle-Ottawa Scale. Meta-analysis was performed using random-effects model (DerSimonian-Laird). Results: We identified 1,847 records, of which 89 studies met inclusion criteria (n=34,156 participants). Meta-analysis of 24 studies showed significant natriuretic increase under digitalis-like compounds influence (SMD = 1.67, 95% CI: 1.52-1.82, p<0.001, I²=68%). Endogenous digitalis-like compound levels were progressively elevated in hypertension (1.87±0.64 vs 0.52±0.18 nmol/L in healthy individuals, p<0.001), heart failure (2.34±0.89 nmol/L), and chronic kidney disease (2.78±1.12 nmol/L). Natriuretic peptides demonstrated coordinated responses with cellular mechanisms: correlation between ANP and Na-K-ATPase activity (r=0.58, p<0.01), BNP and endogenous ouabain levels (r=0.42, p<0.05). Conclusions: The dual regulatory system of water-sodium homeostasis represents an integrated network of mechanisms that coordinate cellular activity and systemic fluid balance through complex pathophysiological interactions. The cellular subsystem (digitalis-like compounds/Na-K-ATPase) is functionally integrated with the systemic subsystem (natriuretic peptides/neurohormonal regulation) to maintain homeostasis. Disruption of this integration underlies the pathogenesis of arterial hypertension, heart failure, and chronic kidney disease. These findings have critical significance for understanding pathophysiology and developing new personalized therapeutic strategies.